Minimal inhibitory concentration (MIC) of sodium hypochlorit against bacterial isolate from equipment in the microbiology laboratory - Mamay, Mamay; Mar’atiningsih, Lia; Atoilah, Elang M.; Mutia, Sifa Rinda (Institute Of Computer Science (IOCS), 2024)
Microbiology laboratory equipment is susceptible to bacterial contamination and therefore has the potential to become a medium for the spread of disease and infection. The existence of a less than sterile microbiological analysis process in the STIKes Karsa Husada Garut Microbiology Laboratory causes bacterial contamination of laboratory equipment such as bacterial analysis that does not comply with standards or the use of less than sterile equipment. To control the spread of contaminants, a decontamination process is required using a chemical disinfectant, namely sodium hypochlorite. Measuring the effectiveness of a disinfectant by looking at or can be determined by the Minimum Inhibitory Concentration (MIC). The aim of this research was to determine the effectiveness of sodium hypochlorite disinfectant in inhibiting the growth of microorganisms in bacterial isolates from the STIKes Karsa Husada Garut Microbiology Laboratory equipment. The data analysis used was analyzed descriptively. The results of this research are the Minimum Inhibitory Concentration (MIC) of sodium hypochlorite disinfectant on bacterial isolates from the STIKes Karsa Husada Garut Microbiology Laboratory equipment at a concentration of 4%. So it can be concluded that sodium hypochlorite disinfectant with a concentration of 4% is effective in inhibiting the growth of microorganisms.